Children's participation in clinical research: factors influencing parental consent. (24th May 2012) - Elemraid, MA; Pollard, K; Thomas, MF; Simmister, C; Spencer, DA; Rushton, SP; Gennery, AR; Clark, JE
Abstract : Background: An important obstacle when undertaking clinical research in children is the consent procedure. Understanding the factors influencing this process is vital in improving children's involvement in clinical research. Objective: To report the rates and causes for recruitment refusal into two studies of childhood pneumonia and empyema and investigate the underlying factors contributing to refusal. Methods: Two paediatric respiratory studies investigating childhood pneumonia and empyema and requiring informed consent were carried out at the same site. During the period from April 2010 to March 2011, the number of eligible children who gave or refused consent for each study was documented. Each research team included a paediatric research nurse and paediatric research registrar (doctor). Information was collected prospectively on each consent refusal. Rates of refusal by role of person taking consent, severity of illness and reason for refusal were then analysed. Results: A total of 116 children were eligible for enrolment into pneumonia study and 28 into empyema study, giving 144 consent procedures. Ten (7%) parents refused the consent. The rate of refusal did not differ between medical and nursing staff. Eighty percent of the children who were not enrolled had severe disease. Refusals were linked with not wanting the child to undergo further investigations, research delaying discharge, and anxiety regarding written consent and length of information sheets. Conclusion: Consent refusal was not related to the role of the person seeking consent. Severity of child's illness appears to determine parent's decision regarding participation in clinical research.